Low-affinity CD4+ T cells are major responders in the primary immune response - Ryan J. Martinez (Nature Portfolio, 2016)
MHC II tetramers are used to study T cell expansion but they preferentially bind high affinity T cell receptors. Here the authors show that T cells with low affinity receptors expand in number along with the T-cell repertoire and might therefore contribute more to the primary immune response than was thought.